Kejadian Kardiovaskular Selamat Perawatan Pasca IMAInferior Dapat Diprediksi Dengan Rasio Tinggi Titik J/Gelombang R - Sonny H Wicaksono; Yoga Yuniadi; Nani Hersunarti (The Indonesian Heart Association, 2009)
Introduction: Some patients with acute inferior ST-Elevation Myocardial Infarction (STEMI) experienced in-hospital events such as Brady-arrhythmias and hypotension after primary angioplasty. Those events have been associated with proximal lesion and larger final infarct size. Some variables associated with such conditions are ischemic preconditioning, hyperglycemia and patterns of initial ECG of J point/R wave ratio > 0,5. We sought to determine variables that can predict in-hospital cardiovascular events in patients with acute inferior STEMI after primary angioplasty.Methods: The present study is a case-control study involving patients with acute inferior STEMI underwent primary angioplasty, grouped based on presence of in-hospital cardiovascular event. Univariate and multivariate analyses were conducted to variables related with in-hospital cardiovascular events after primary angioplasty.Results: There were total 96 subjects (48 cases and 48 controls) with acute inferior STEMI underwent primary angioplasty recruited for this study. Multivariate analysis revealed ratio of J point/R wave >0,5 is significant predictor for in-hospital cardiovascular events after primary angioplasty (OR 9,532; 95% CI: 3,406-26,678; p<0,001). Conclusion: In-hospital cardiovascular events in patients with inferior STEMI after primary angioplasty can be predicted with initial ECG patterns ratio of J point/R wave > 0,5.